Upward and downward social mobility probabilities have converged for men and women - Nicolas Legewie; Sandra Bohmann (DIW Weekly Report, 2018)
This study investigates professional social mobility, i.e., changes in one's occupational status compared to that of their parents. It uses data from the German Socio-Economic Panel (Sozio-oekonomisches Panel, SOEP) on middle-aged, western Germans who were born between 1939 and 1971. On average, social status relative to parents has increased (absolute social mobility). However, looking at how positions change from parents to their children relative to their respective cohorts (relative social mobility) shows that, on average, little has changed in this respect since the Second World War. A person is still much more likely to achieve a position in the top status group if the parents already had such a position. Looking at specific social groups, the picture is more differentiated. Mobility patterns for men and women have largely converged during the observation period: men experience downward mobility more often than before and women experience upward mobility more frequently.
Keywords: J62; Y10; 330; intergenerational mobility; status mobility